Analisis Pengaruh Likuiditas, Ukuran perusahaan, dan Konservatisme Akuntansi terhadap Kualitas Laba dengan Profitabilitas sebagai Variabel Moderasi - Olga Welly Charisma; Dhini Suryandari (Universitas Katolik Soegijapranata Semarang, 2021)
The purpose of this study is to examine and analyze the effect of liquidity, firm size, and accounting conservatism on earnings quality by using profitability as a moderating variable. The population in this study are mining companies listed on the Indonesia Stock Exchange for the period 2017-2019. Using purposive sampling technique, as much 62 firm observations were gathered and used for the test of hypothesis. The analysis technique used is descriptive statistical analysis and inferential statistical analysis with moderated analysis regression interaction test as the moderating regression analysis. The results show that accounting conservatism has a positive effect on earnings quality. On the contrary, liquidity and firm size have no effect on earnings quality. In addition, profitability does not moderate the relationship between liquidity and earnings quality, profitability does not moderate the relationship between firm size and earnings quality, but profitability weakens the relationship between accounting conservatism and earnings quality.